Cherished theme becomes a book. Silence of the guns : the history of the Long Toms of the Anglo-Boer War , Louis Changuion : book review (Historia, 2021)
On the whole An African classical age is a solid work. The only point of criticism could perhaps be references to contemporary regional entities. Since 1994 names such as the Transvaal and Natal have vanished. What used to be the Transvaal is today subdivided into the Northern Province, Mpumalange, the Northwest Province and Gauteng. Similarly Natal today comprises the province known as KwaZulu Natal. The same changes may have taken place in South Africa’s neighbouring states. It is likely that the old terminology for place names will still persist for some time to come amongst subject specialists. Somewhere they will however have to make the necessary changes. For the rest Ehret’s work deserves praise for opening up some interesting insights on our perspectives of the local African past at the start of yet another millenniumin the history of the world.
Keywords: African classical age; student of linguistics; Boer forces